ACTN3: More than Just a Gene for Speed - Pickering, Craig; Kiely, John (Frontiers in Physiology, 2017)
Over the last couple of decades, research has focused on attempting to understand the genetic influence on sports performance. This has led to the identification of a number of candidate genes which may help differentiate between elite and non-elite athletes. One of the most promising genes in that regard is ACTN3, which has commonly been referred to as “a gene for speed”. Recent research has examined the influence of this gene on other performance phenotypes, including exercise adaptation, exercise recovery, and sporting injury risk. In this review, we identified 19 studies exploring these phenotypes. Whilst there was large variation in the results of these studies, as well as extremely heterogeneous cohorts, there is overall a tentative consensus that ACTN3 genotype can impact the phenotypes of interest. In particular, the R allele of a common polymorphism (R577X) is associated with enhanced improvements in strength, protection from eccentric training-induced muscle damage, and sports injury. This illustrates that ACTN3 is more than just a gene for speed, with potentially wide-ranging influence on muscle function, knowledge of which may aid in the future personalisation of exercise training programmes.